2003
DOI: 10.2165/00128071-200304030-00004
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Pruritus

Abstract: With the advent of highly active antiretroviral therapy (HAART), life-threatening opportunistic infection has become less common in patients with HIV infection and longevity has increased dramatically. With increased longevity, the problems of living with a chronic disease have become more prominent in this patient population. Disorders such as fat redistribution and metabolic abnormalities can result from antiviral medications and from HIV disease itself. Pruritus is one of the most common symptoms encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…This condition is found in more than 20% of people with HIV-1 [41]. It presents mainly on extremities, and it denotes one of the main causes of pruritus in AIDS patients [42]. Its pathogenesis has been suggested to include changes in the microcirculation, the nutrient supply of the skin, and in the production of sweat and oil in the skin [43].…”
Section: Reviewmentioning
confidence: 99%
“…This condition is found in more than 20% of people with HIV-1 [41]. It presents mainly on extremities, and it denotes one of the main causes of pruritus in AIDS patients [42]. Its pathogenesis has been suggested to include changes in the microcirculation, the nutrient supply of the skin, and in the production of sweat and oil in the skin [43].…”
Section: Reviewmentioning
confidence: 99%
“…In another study conducted in Brazil, 10–25 % of unselected patients starting ART developed IRIS with 52–78 % of these patients presenting with cutaneous features [ 1 , 9 ]. Tinea-IRIS lesions can be visible on patient’s skin, and despite not being associated with mortality can cause a decrease in the quality of life [ 10 ]. Moreover, it requires a high index of suspicion to be treated.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pruritus has been – and still is – a common symptom in patients with human immunodeficiency virus (HIV) even in the new era of highly active antiretroviral therapy (HAART) and combination antiretroviral therapy (cART) . A study in the United States in 2012 has reported a 45% prevalence rate in 201 HIV‐infected patients, an estimate which is close to the 31% documented by a study in Spain on 303 HIV‐infected patients in 2003 …”
Section: Main Textmentioning
confidence: 91%
“…A range of primary skin disorders (such as xerosis, atopic dermatitis, seborrheic dermatitis, psoriasis, infections like scabies or dermatophyte infections, etc.) may be the etiology of pruritus or might be the reason for exacerbation, relapse, or more severe manifestations of an underlying skin disorder . Chronic pruritus may also be associated with systemic disorders in HIV‐infected patients (e.g.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation